2016
DOI: 10.4236/ampc.2016.68024
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Improvement of PEDOT:PSS Transparent Conductive Film Prepared by Ink-Jet Printing

Abstract: Recently, a high-performance and low-priced transparent conductive film has been expected to be developed because flexible devices produced using organic materials have been actively studied. An indium tin oxide (ITO) thin film, which has been generally used as a material for a transparent conductive film, has problems, such as fragility to bending stress and depletion of the resource. The present study used poly(3, 4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS), an organic electroconductive mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a previous study, by spraying the polar solvent on a PEDOT:PSS thin film after each time a layer was printed, the characteristics of the PEDOT:PSS thin film were improved in terms of resistivity and transmittance [24]. However, there was a limitation in uniformly applying a polar solvent by artificially spraying it.…”
Section: Examination Of the Application Methods Of A Polar Solventmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, by spraying the polar solvent on a PEDOT:PSS thin film after each time a layer was printed, the characteristics of the PEDOT:PSS thin film were improved in terms of resistivity and transmittance [24]. However, there was a limitation in uniformly applying a polar solvent by artificially spraying it.…”
Section: Examination Of the Application Methods Of A Polar Solventmentioning
confidence: 99%
“…For the conditions of UV/O 3 cleaning, the UV radiation distance was 30mm, the output of a low-pressure mercury lamp was 40 W, and the cleaning time was 20 min. Like a previous study, PEDOT:PSS thin films were formed by printing two to four times [24]. To evaporate the additives that remained in the thin film as impurities after it was formed and adversely affected the conductivity, the thin film was annealed for 30 min after each time a layer was printed and for 60 min after the entire printing process was completed, using a constant-temperature drying oven (EOP-300B; As One Co., Ltd.).…”
Section: Production and Evaluation Of A Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…If we can solve these issues and produce a practical transparent conductive film, it will become possible to manufacture flexible devices, including wiring and electrodes, using only printing technology. So far, we have found that cleaning the substrate with ultraviolet/ozone (UV/O 3 ) and post-deposition annealing and treatment using polar solvents are effective for PEDOT:PSS thin films [24] [25]. The characteristics of the thin film were also improved by changing the ink solvent from ethanol to dimethyl sulfoxide (DMSO).…”
mentioning
confidence: 99%
“…To determine some origin behind the improved Seebeck coefficient, UV-Vis-NIR absorption spectra were obtained for the CX and SX films. [463][464][465] As shown below in In literature a reduction of charge carriers as indicated by an emergence or increased quantity of polarons or neutral thiophene absorption intensity is usually accompanied by improved Seebeck coefficient in PEDOT:PSS based films. 128,[468][469][470][471] As shown in This is most probably due to the films being thicker than the C1 and C2.…”
Section: Proposed Mechanisms For Increased Seebeck Coefficientmentioning
confidence: 94%